Truncated C-terminus of fibrillin-1 induces Marfanoid-progeroid-lipodystrophy (MPL) syndrome in rabbit - Mao Chen; Bing Yao; Qiangbing Yang; Jichao Deng; Yuning Song; Tingting Sui; Lina Zhou; HaoBing Yao; Yuanyuan Xu; Hongsheng Ouyang; Daxin Pang; Zhanjun Li; et al. (The Company of Biologists, 2018)
Various clinical differences have been observed between patients with the FBN1 gene mutation and those with the classical Marfan phenotype. Although FBN1 knockout (KO) or dominant-negative mutant mice are widely used as an animal model for Marfan syndrome (MFS), these mice cannot recapitulate the genotype/phenotype relationship of Marfanoid-progeroid-lipodystrophy (MPL) syndrome, which is caused by a mutation in the C-terminus of fibrillin-1, the penultimate exon of the FBN1 gene. Here, we describe the generation of a rabbit MPL model with C-terminal truncation of fibrillin-1 using a CRISPR/Cas9 system. FBN1 heterozygous (FBN1 Het) rabbits faithfully recapitulated the phenotypes of MFS, including muscle wasting and impaired connective tissue, ocular syndrome and aortic dilation. Moreover, skin symptoms, lipodystrophy, growth retardation and dysglycemia were also seen in these FBN1 Het rabbits, and have not been reported in other animal models. In conclusion, this novel rabbit model mimics the histopathological changes and functional defects of MPL syndrome, and could become a valuable model for studies of pathogenesis and drug screening for MPL syndrome.